2009
DOI: 10.1172/jci37262
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage deficiency of p38α MAPK promotes apoptosis and plaque necrosis in advanced atherosclerotic lesions in mice

Abstract: ER stress occurs in macrophage-rich areas of advanced atherosclerotic lesions and contributes to macrophage apoptosis and subsequent plaque necrosis. Therefore, signaling pathways that alter ER stress-induced apoptosis may affect advanced atherosclerosis. Here we placed Apoe -/-mice deficient in macrophage p38α MAPK on a Western diet and found that they had a marked increase in macrophage apoptosis and plaque necrosis. The macrophage p38α-deficient lesions also exhibited a significant reduction in collagen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 60 publications
6
128
4
1
Order By: Relevance
“…This concept fits well with our overall concept that individual proapoptotic hits are subthreshold (15) and that multiple subthreshold hits - in this case, all 3 of the CaMKII pathways depicted in Figure 10 - are necessary for apoptosis. In addition to the activation of multiple subthreshold proapoptotic pathways, the multihit concept also involves suppression of compensatory cell survival pathways, such as those involving IFN-β and Akt-p38α, that are often induced in parallel with UPR activation (23,60).…”
Section: Discussionmentioning
confidence: 99%
“…This concept fits well with our overall concept that individual proapoptotic hits are subthreshold (15) and that multiple subthreshold hits - in this case, all 3 of the CaMKII pathways depicted in Figure 10 - are necessary for apoptosis. In addition to the activation of multiple subthreshold proapoptotic pathways, the multihit concept also involves suppression of compensatory cell survival pathways, such as those involving IFN-β and Akt-p38α, that are often induced in parallel with UPR activation (23,60).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that p38MAPK plays a critical role in suppressing ER stress-induced macrophage apoptosis in vitro and advanced lesional macrophage apoptosis in vivo (35). On the contrary, p38MAPK also has a pro-apoptotic role in maintaining homeostasis under various stresses.…”
Section: F and G) 3) Mppmentioning
confidence: 98%
“…While the increase in lesion size was not significant, there was certainly no decrease as might have been expected. Instead, there was marked increase in apoptotic markers, necrotic areas, a decrease in collagen deposition, and thinning of the fibrous cap (1583). Uptake of apoptotic cells by macrophages (efferocytosis) triggers an antiinflammatory release of IL-10 and TGF␤ dependent on p38 (473).…”
Section: %mentioning
confidence: 99%
“…Other examples of a need for balanced, modest activation have been reported, as in the limited oxidative stress required to activate Nrf2. Some NF-B pathway activity is protective (as macrophage-specific IKK2 KO caused increased atherosclerosis) and the absence of the MAPK p38 in macrophages greatly increased apoptosis and necrosis with accelerated atherosclerosis (1583). This may also explain why KO of MAPK phosphatase 1 (MKP-1), which inhibits p38, actually decreased plaque size (see TABLE 1).…”
Section: Er Stress In Foam Cellsmentioning
confidence: 99%